Tautan Kasih - FPHP community service / Abdul Rahman Ahmad Rozali and Khairil Anuar Bahari - Ahmad Rozali, Abdul Rahman; Bahari, Khairil Anuar (Faculty of Hotel & Tourism Management, 2007)
Malaysia has been a major supporter of Corporate Social Responsibility (CSR) concept, with the government promoting and underscoring the key role of CSR as contributing factors to national growth. As such, UiTM Penang also has devoted several programs toward promoting child-friendly CSR. "UiTM Penang devoted several programs towards child- friendly CSR" Located in Rumah Kanak-Kanak Taman Bakti, Kepala Batas, the Faculty of Hotel and Tourism Management (FPHP) UiTM Penang organized a community service on the 20th December 2018 from 9.00 am to 2.00 pm. Led by Chef Abdul Rahman, the program involved a joint collaboration of 78 lecturers and staffs from FPHP and several companies including Syarikat Ayam Bismi, Farm Fresh Sdn Bhd. SN Craft Ventures, Seberang Perai Utara Health Office , Kepala Batas Dental Clinic and Sinar Harian.